2022
DOI: 10.3389/fnagi.2022.914360
|View full text |Cite
|
Sign up to set email alerts
|

Atrial cardiopathy and cognitive impairment

Abstract: Cognitive impairment involves complex interactions between multiple pathways and mechanisms, one of which being cardiac disorders. Atrial cardiopathy (AC) is a structural and functional disorder of the left atrium that may be a substrate for other cardiac disorders such as atrial fibrillation (AF) and heart failure (HF). The association between AF and HF and cognitive decline is clear; however, the relationship between AC and cognition requires further investigation. Studies have shown that several markers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Low cardiac output of HF patients is one of the key reasons for cerebral hypoperfusion, which is critical to cognitive function. Another cause of CCH is the impairment of vascular autoregulation after HF ( 34 , 35 ). Disruption of vascular autoregulation impairs vasodilation function, making it difficult to maintain sufficient CBF in a state of low cardiac output.…”
Section: Risk Factors Of Cardiogenic Dementiamentioning
confidence: 99%
“…Low cardiac output of HF patients is one of the key reasons for cerebral hypoperfusion, which is critical to cognitive function. Another cause of CCH is the impairment of vascular autoregulation after HF ( 34 , 35 ). Disruption of vascular autoregulation impairs vasodilation function, making it difficult to maintain sufficient CBF in a state of low cardiac output.…”
Section: Risk Factors Of Cardiogenic Dementiamentioning
confidence: 99%
“…Potentially, this property might help with screening for early signs of cognitive dysfunction [ 44 ]. Several markers indicative of atrial cardiomyopathy, a structural and functional disorder of the left atrium, such as increased brain natriuretic peptide and left atrial enlargement, were also associated with an increased risk for cognitive impairment [ 45 ].…”
Section: Cognitive Decline and Dementia In Common Cardiac Disordersmentioning
confidence: 99%
“…Consequently, continuous anticoagulant medication is required in all three atrial fibrillation entities if CHA 2 DS 2 -VASc Score ≥ 2 [ 68 ]. Previous studies have revealed that atrial cardiomyopathy, even in the absence of atrial fibrillation, is a risk factor for stroke and cognitive impairment [ 71 , 72 , 73 ]. The detection rate of new-onset atrial fibrillation after cryptogenic stroke ranged between 5% and 25%, depending on the heart-rhythm monitoring method [ 74 , 75 , 76 , 77 ].…”
Section: Biomarkers Of Atrial Cardiomyopathy: Serological Electrophys...mentioning
confidence: 99%